2022
DOI: 10.1109/access.2022.3169285
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of User’s Intention to Use Metaverse System in Medical Education: A Hybrid SEM-ML Learning Approach

Abstract: Date of publication xxxx 00, 0000, date of current v ersion xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(140 citation statements)
references
References 68 publications
(85 reference statements)
1
136
0
3
Order By: Relevance
“…In this context, it has been concluded that the usefulness of the metaverse system and the fact that people think they will benefit affect their intentions, which are the pioneers of active use of the system ( Venkatesh & Davis, 2000;Davis, 1989;Park & Kang, 2021;Yorulmaz & Alnıpak, 2020;Akour et. al., 2022;Almarzouqi et. al.. 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been concluded that the usefulness of the metaverse system and the fact that people think they will benefit affect their intentions, which are the pioneers of active use of the system ( Venkatesh & Davis, 2000;Davis, 1989;Park & Kang, 2021;Yorulmaz & Alnıpak, 2020;Akour et. al., 2022;Almarzouqi et. al.. 2022).…”
Section: Discussionmentioning
confidence: 99%
“…'s (2022) study aims to investigate the students' perceptions of the metaverse system for educational purposes in the Gulf area. Almarzouqi et. al.…”
Section: Yavuz Toramanmentioning
confidence: 99%
“…ii The amount of these estimate functions derived from the matrix can be obtained characteristically, which will surpass the least number of the X and Y variables. The majority of the studies conducted in the study of the information systems and the EMR systems are dependent on the tools that include partial least squares (PLS) and structural equation modeling (SEM), regression which is vital in testing the causal relationships [75][76][77][78]. Despite the universal acceptance of the application of this method, there is a possibility that it can lead to the oversimplification of the calculation's complexities during the decision-making process [79,80].…”
Section: Plos Onementioning
confidence: 99%
“…It has been used as the technology acceptance and adoption (i.e., [75][76][77][81][82][83][84]), this is mainly because it can outperform other modeling tools like the lined modeling, regression, and the PLS-SEM. It is majorly a result of its ability to fully identify both the validity prediction and the linear relationships that are coupled with the fast learning and accuracy predictions, the high prediction accuracy and the accuracy in the validity prediction, exerts the dominance in reliability over the PLS-SEM and regression, ANN is considered as less restrictive when applied-with limited mandate on the factor loadings, assumption normality, homoscedasticity, linearity, sample size, sample error and the lack of power [5,78,80], fault tolerance-ANN, however, is a model that can accommodate all the functions samples with an ore individual differences [85] and it also has a considerably good capability generalization-it is robust against the missing data or noisy data [86]. These considered attractive functions of the model are among the contributing factors to its versatility in application.…”
Section: Plos Onementioning
confidence: 99%
“…Gambar 1. Analisis VR dan pendidikan publikasi dari 2020 hingga 2022 (Lee & Hwang, 2022) Kembali merujuk pada pengertian metaverse adalah dunia digital yang dapat diakses melalui lingkungan virtual (Almarzouqi et al, 2022). Ini didirikan melalui penggabungan realitas fisik dan digital yang hampir ditingkatkan.…”
Section: Daftar Pustakaunclassified